Analisis PAD Dan Belanja Pegawai Terhadap Tingkat Kemandirian Keuangan Daerah Di Provinsi Jawa Timur 2019-2020 - Monica Vidia Putri Sefira; Gideon Setyo Budiwitjaksono (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
This study aimed to analyze the effect of local revenue and personnel expenditures on the level of regional financial independence in East Java 2019-2020. This research used quantitative research methods using secondary data derived from the APBD reports belonging to districts/cities in East Java Province 2019-2020 which is on the website of Ministry of Finance DJPK. The sample in this study was obtained through purposive sampling technique with a total of 33 research samples. The analysis technique in this study used multiple linear regression analysis with the help of SPSS software. The results of the study indicate that local revenue has a significant effect on the level of regional financial independence, while personnel expenditures have a simultaneous but not significant effect on the level of regional financial independence. Keywords: Regional Independence Level, Regional Original Income, Employee Expenditure